2015
DOI: 10.1371/journal.pone.0129724
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro-Stimulated IL-6 Monocyte Secretion and In Vivo Peripheral Blood T Lymphocyte Activation Uniquely Predicted 15-Year Survival in Patients with Head and Neck Squamous Cell Carcinoma

Abstract: The study was performed in order to determine whether peripheral blood monocyte in vitro function, and lymphocyte in vivo activation at diagnosis, was associated with HPV tumor infection status and 15-year survival in head and neck squamous cell carcinoma (HNSCC) patients. Sixty-five patients from a consecutive cohort of newly diagnosed HNSCCs, together with 18 control patients, were included in the study. Monocyte responsiveness was assessed by measuring monocyte in vitro interleukin (IL)-6 secretions after 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
(50 reference statements)
0
10
1
Order By: Relevance
“…The IL‐6 monocyte secretory levels were scored following the relative difference between the LPS pathogen‐associated molecular pattern (PAMP) and spheroid‐associated response, which consisted of several possible stimuli such as damage‐associated molecular pattern (DAMP) and secretory products of the spheroid cells . The current study cannot specifically answer this question, but do support a role of MNPs in the cancer trajectory.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The IL‐6 monocyte secretory levels were scored following the relative difference between the LPS pathogen‐associated molecular pattern (PAMP) and spheroid‐associated response, which consisted of several possible stimuli such as damage‐associated molecular pattern (DAMP) and secretory products of the spheroid cells . The current study cannot specifically answer this question, but do support a role of MNPs in the cancer trajectory.…”
Section: Discussionmentioning
confidence: 85%
“…We have previously shown that HPV+ compared to HPV‐ HNSCC patients had lower in vitro monocyte lipopolysaccharide (LPS)‐stimulated interleukin (IL)‐6 responses. A high LPS‐stimulated in vitro monocyte IL‐6 response furthermore predicted decreased survival, to some extent independent of HPV infection status . A high percentage of CD71‐positive T lymphocytes also predicted an impaired prognosis.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In the present study, the expression of IL-6 mRNA and protein in liver tissues, PBMCs and serum from patients with liver cirrhosis was higher than in patients with liver fibrosis, suggesting that inflammation may be aggravated during the transformation from liver fibrosis to cirrhosis. Upregulation of IL-6 may be caused by the activation of monocytes and lymphocytes, which can secrete abundant IL-6 factors and produce antigen immune responses (32).…”
Section: Discussionmentioning
confidence: 99%